2015
DOI: 10.1103/physrevlett.114.255002
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Scale Interactions between Electron and Ion Scale Turbulence in a Tokamak Plasma

Abstract: Multiscale gyrokinetic turbulence simulations with the real ion-to-electron mass ratio and β value are realized for the first time, where the β value is given by the ratio of plasma pressure to magnetic pressure and characterizes electromagnetic effects on microinstabilities. Numerical analysis at both the electron scale and the ion scale is used to reveal the mechanism of their cross-scale interactions. Even with the real-mass scale separation, ion-scale turbulence eliminates electron-scale streamers and domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(167 citation statements)
references
References 22 publications
8
157
2
Order By: Relevance
“…Recent multi-scale gyrokinetic (GK) simulations involving both ion and electron scale fluctuations showed that the ETG turbulence might be suppressed when ion scale turbulence is strongly excited. 2,3 On the contrary, when ion scale turbulence is suppressed by strong E Â B shear flows, electron scale turbulence is dominated by the streamer and thus becomes the main channel of the electron heat losses. 4 In fact, transport barriers 5,6 and spherical tokamaks 7 are characterized by strong E Â B shear flows and ion heat transport at neoclassical levels, and the remaining anomalous electron heat transport is often discussed based on the ETG turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Recent multi-scale gyrokinetic (GK) simulations involving both ion and electron scale fluctuations showed that the ETG turbulence might be suppressed when ion scale turbulence is strongly excited. 2,3 On the contrary, when ion scale turbulence is suppressed by strong E Â B shear flows, electron scale turbulence is dominated by the streamer and thus becomes the main channel of the electron heat losses. 4 In fact, transport barriers 5,6 and spherical tokamaks 7 are characterized by strong E Â B shear flows and ion heat transport at neoclassical levels, and the remaining anomalous electron heat transport is often discussed based on the ETG turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Since these nonlinear gyrokinetic simulations can require 10 3 processor-hours or more (even 10 7 and beyond in some cases [65][66][67][68] ) to calculate the statistics at a single location in the plasma, reduced models of the turbulence have been developed which can make predictions on the processorminute or less timescale, to facilitate practical transport modeling with feasible resource requirements. The general approach of most such models is to decompose the turbulent fluxes into two components along the lines of (using the ion energy flux Q i as an example)…”
Section: Basics Of Turbulence and Transport Modeling In Magneticmentioning
confidence: 99%
“…A third, even more computationally expensive avenue of approach would be to investigate the impact of multiscale simulations which self-consistently incorporate q e -scale ETG fluctuations into these q i -scale simulations. [65][66][67][68][140][141][142][143][144][145][146] Other research avenues are possible as well. However, for the goals of this paper, it should be clear how utilizing a variety of local validation metrics for multiple predicted quantities can be employed to test model fidelity and our physical understanding at a level not possible by earlier global metrics.…”
Section: Fluctuation Sensitivity Plots and Validation Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] Proper characterization of these effects requires "multi-scale" simulations (with realistic electron mass), which simultaneously capture the electron and ion scales. It has been shown that in an Alcator C-Mod L-mode plasma, the inclusion of multiscale effects can resolve discrepancies between values of ion heat flux, electron heat flux, and perturbative thermal diffusivity from experimental measurements and those calculated from ion-scale GYRO simulations.…”
Section: Introductionmentioning
confidence: 99%